TO STAY OR NOT TO STAY: THAT IS A QUESTION - Ramanauskaite, Egidija; Vaisnys, Rimas (European Scientific Journal, ESJ, 2015)
Emigration and immigration, particularly of young individuals, raise social, economic, and cultural problems for both the recipient and donor countries. Substantial fluctuations in these rates make coherent adjustment and planning for the resulting social processes at best difficult, at worst ineffective. We have undertaken a study of the behavior and motivation of university students as they enter the university educational system and begin their studies with an aim to provide a measure of predictability in this phenomenon. To identify important factors which influence a young person’s choice between continuing studies in a native university and a foreign one we have carried out a longitudinal study of about fifty Lithuanian students at three time instances: At t0, the time they choose between emigration or staying in their home country for their university education; at t1, soon after they arrive and first encounter their chosen environment; at t2, some six months or so after their direct experience of their chosen environment. The investigation was carried out with respondents drawn from universities in Lithuania and Great Britain. The information was collected through in-depth interviews using ethnographic techniques, initiated with a questionnaire designed to identify some four hundred binary values but allowing additional exploration of naturally arising motivational factors.